Measurement of Bradykinin Formation and Degradation in Blood Plasma: Relevance for Acquired Angioedema Associated With Angiotensin Converting Enzyme Inhibition and for Hereditary Angioedema Due to Factor XII or Plasminogen Gene Variants - Marceau, François; Rivard, Georges E.; Gauthier, Julie M.; Binkley, Karen E.; Bonnefoy, Arnaud; Boccon-Gibod, Isabelle; Bouillet, Laurence; Picard, Matthieu; Levesque, Ghislain; Elfassy, Hannah Laure; Bachelard, Hélène; Hébert, Jacques; et al. (Frontiers in Medicine, 2020)
Bradykinin (BK)-mediated angioedema (AE) states are rare acquired or hereditary conditions involving localized edema of the subcutaneous and submucosal tissues. Citrated plasma from healthy volunteers or patients with hereditary angioedema (HAE) with normal level of C1-inhibitor (C1-INH) was used to investigate pathways of BK formation and breakdown relevant to AE physiopathology. The half-life of BK (100 nM) added to normal plasma was 34 sec, a value that was increased ~12-fold when the angiotensin converting enzyme (ACE) inhibitor enalaprilat (130 nM) was added (enzyme immunoassay measurements). The BK half-life was similarly increased ~5 fold following 2 daily oral doses of enalapril maleate in healthy volunteers, finding of possible relevance for the most common form of drug-associated AE. We also addressed the kinetics of immunoreactive BK (iBK) formation and decline, spontaneous or under 3 standardized stimuli: tissue kallikrein (KLK-1), the particulate material Kontact-APTT™ and tissue plasminogen activator (tPA). Relative to controls, iBK production was rapid (10-20 min) and very intense in response to tPA in plasma of female heterozygotes for variants in gene F12 coding for factor XII (FXII) (p.Thr328Lys, 9 patients; p.Thr328Arg, one). An increased response to Kontact-APTT™ and an early tPA-induced cleavage of anomalous FXII (immunoblots) were also observed. Biotechnological inhibitors showed that the early response to tPA was dependent on plasmin, FXIIa and plasma kallikrein. Results from post-menopausal and pre-menopausal women with HAE-FXII were indistinguishable. The iBK production profiles in 7 patients with the plasminogen p.Lys330Glu variant (HAE-PLG) did not significantly differ from those of controls, except for an unexpected, rapid and lanadelumab-resistant potentiation of KLK-1 effect. This enzyme did not cleave plasminogen or factor XII, suggesting a possible idiosyncratic interaction of the plasminogen pathogenic variant with KLK-1 activity. KLK-1 abounds in salivary glands and human saliva, hypothetically correlating with the clinical presentation of HAE-PLG that includes the swelling of the tongue, lips and contiguous throat tissues. Samples from HAE patients with normal C1-INH levels and F12 gene did not produce excessive iBK in response to stimuli. The ex vivo approach provides physiopathological insight into AE states and supports the heterogeneous physiopathology of HAE with normal C1-INH.